Técnica quirúrgica y sus complicaciones en colecistectomía laparoscópica - Balseca Zamora, Roosevelt Joel (2024)
Laparoscopic cholecystectomy is a surgical technique to remove the gallbladder with a pathological condition, with the use of a lens and small incisions, making it less invasive and superior to open cholecystectomy. Currently, with the development of a society that focuses on aesthetics, even less invasive techniques have been designed with the use of fewer ports, giving patients an even more aesthetic alternative, but it is always necessary to take into account the underlying pathology and the search for the health of the patient, which will always be above the desire for perfection. Objective: To carry out an updated literature review on how surgical technique influences postoperative complications of laparoscopic cholecystectomy, in order to standardize therapeutic protocols that improve the prognosis of these patients. Methods: A descriptive study was carried out by means of a literature review, in which various scientific sources were examined, including research results, linked to the subject and reporting results of the application of different surgical techniques. Results: It was demonstrated that laparoscopic cholecystectomies with the use of three and four ports showed the same number of postoperative complications, being safe for application in patients without contraindications for a laparoscopic technique. In terms of aesthetics, the use of fewer ports slightly outperforms three - port cholecystectomy, provided that the skill of a surgeon, familiarity and comfort with the technique are taken into account, as without these conditions its application would be counterproductive. Conclusions: This study provided a clearer picture of the similarities in postoperative complications in patients undergoing four - and three - port laparoscopic cholecystectomy, giving the surgeon the option to safely apply either technique depending on his or her comfort and familiarity with the due technique.